x/6=-43

Simple and best practice solution for x/6=-43 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x/6=-43 equation:


x in (-oo:+oo)

x/6 = -43 // + 43

x/6+43 = 0

1/6*x+43 = 0 // - 43

1/6*x = -43 // : 1/6

x = -43/1/6

x = -258

x = -258

See similar equations:

| 41x=1974 | | -7-7(-4x-9)=168 | | 6z^2-7z+12=0 | | x+.06x=27120 | | 10sinx-1=0 | | 41x=1975 | | 12(x^3)=60(x^2)+75x | | 3x-13=-22 | | X(10x-7)+11(10x-7)=0 | | 5/3x^3-10x=0 | | -3+10y+7=15+14y-31 | | 105=-5x+6(3x-2) | | 5x-9=3x+21 | | x^3-2x^2-x^1=0 | | 3x+10=-7x | | 2(0)=0 | | 2(2)=0 | | 12+5z=-13 | | 4x(6x^2-13x-8x)=0 | | 34x-16=x+50 | | 1/2x4=2/3x | | 63x=-3x+660 | | -6+6x=-3x+660 | | 9x-7=6x-34 | | x-(-18)=19 | | 180-4X=3X^2+5 | | 2(x+10)=-3x | | 5x+2-2x=11 | | 2m^2-6m-24=0 | | 3(2a-4/b^2) | | x+10=-3x+14 | | 5x^2-16-x^2/2 |

Equations solver categories